1978
DOI: 10.1212/wnl.28.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated immunity to measles virus in multiple sclerosis

Abstract: The blastogenic transformation of lymphocytes on exposure to antigen was used to investigate cell-mediated immune responses to viruses implicated in the pathogenesis of multiple sclerosis. In 12 patients with "early" multiple sclerosis, lymphocyte reactivity to measles virus, parainfluenza virus, and vaccinia virus did not differ significantly from reactivity in a healthy control group. However, there was a significant inverse correlation between the lymphocyte blastogenic response to measles and vaccinia viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Symington and MacKay [1978] and Walker and Cook [1979] observed that the level of MIF pro duced in response to measles virus corre lated with the activity of the disease. Detels et al [1981] later confirmed this observa tion.…”
Section: Stimulation Assays: Search For the Elusive Ms-specific Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…Symington and MacKay [1978] and Walker and Cook [1979] observed that the level of MIF pro duced in response to measles virus corre lated with the activity of the disease. Detels et al [1981] later confirmed this observa tion.…”
Section: Stimulation Assays: Search For the Elusive Ms-specific Antigenmentioning
confidence: 99%
“…The results have been variable. For example, measles-virus-in duced blastogenesis has been reported to be equal in MS and control lymphocytes [Dau and Peterson, 1970;Knowles and Saunders, 1970;Cunningham-Rundles et al, 1977;Ste wart et al, 1977;Symington and MacKay, 1978]. In other studies, the response of MS lymphocytes to measles virus was weaker than that of control lymphocytes [McFar land and McFarlin, 1979;Illonen et al, 1981;Sagar et al, 1981] and further studies have shown that MS lymphocytes responded more strongly than control lymphocytes [Walker and Cook, 1979;Walker et al, 1982], Reports involving blast transformation to neural antigens also reveal many inconsis tencies, however, the majority of reports sug gest that MS lymphocytes react to MBP [Colby et al, 1977;Gosseye-Lissoir et al, 1977;Hughes et al, 1977;Lisak and Zwei man, 1977;Lisak et al, 1981;Wicher et al, 1981;Wicher and Holub, 1982;Frick, 1982] as well as cerebrosides and gangliosides [Offner and Konat, 1980;Frick, 1982].…”
Section: Stimulation Assays: Search For the Elusive Ms-specific Antigenmentioning
confidence: 99%
“…MS may not have a single cause, but it is generally believed that au toimmune or dysimmune factors play a cen tral role in its pathogenesis. Viral agents [62], association with specific HLA antigens and defective T cell function [40,63], auto antibodies to basic protein of myelin [64], IgG antibodies blocking electrical activity in frog spinal cord [65] and IC [41] have been implicated in its pathogenesis and the dis ease is often associated with other autoim-protocols appear to be useful in MS. Dau et al [24] suggest a series of PE sessions carried out twice weekly for 3 weeks and then weekly for 5 weeks: PE is combined with prednisone 60-80 mg daily and cyclophos phamide 2-3 mg/kg BW daily.…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…MS may not have a single cause, but it is generally believed that autoimmune or dysimmune factors play a central role in its pathogenesis. Viral agents [62], association with specific HLA antigens and defective T cell function [40, 631, autoantibodies to basic protein of myelin [641, IgG antibodies blocking electrical activity in frog spinal cord [65] and IC [41] have been implicated in its pathogenesis and the disease is often associated with other autoim- [69] and adequate controlled trials requested [70]. A number of anecdotal and uncontrolled reports seem to justify the continuation of this mode of therapy (ta-bleIII), which seems to be of clinical and electrophysiological benefit [68].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%